Extraction of essential oils from ginger rhizome using steam distillation method - Khairu Aizam, Ibrahim (2006)
Essential oils are highly concentrated essences of aromatic plants. It can be extracted using a variety of methods such as steam distillation and solvent extraction. Essential oils have a very high commercial value due to its therapeutic properties. It is widely used in aromatherapy, medicine and as well as flavoring food and drink industries. To get the approximately pure essential oil from raw material, conventional extraction technique like steam distillation is used. Steam distillation is unlikely solvent extraction. This is because steam distillation is to produce essential oils but solvent extraction will produce oleoresin. Pure essential oil can be derived from a part of ginger plant that is the ginger rhizome by using steam distillation method. The extraction of the ginger essential oils began when steam contact to the ginger in the extraction tank. The steam carried out the essential oils from the ginger out of the rhizome and go through the condenser. Then, the steam with the essential oils will be condensed into liquid phase and will be collected in the beaker. Lastly, the two liquids will be separated. To get high quality and quality of essential oils, the fire from burner that burned the tank and produce steam in the tank must be well controlled. Apart from being effective, this study might as well discover potential savings in its operational cost and also environmental friendly.